FOOD COPING STRATEGY RUMAH TANGGA SASARAN PENERIMA MANFAAT BERAS SEJAHTERA DI KABUPATEN PRINGSEWU - Tyas Sekartiara Syafani; Wuryaningsih Dwi Sayekti; Wan Abbas Zakaria (Indonesian Journal of Socio Economics, 2019)
This study aims to analyze food coping strategies of households and relationship between household characteristics and food coping strategy of targeted household of prosperous rice (Rastra) beneficiaries in Pringsewu District. The research uses survey methods. There are four villages as research locations Fajar Baru and Kemilin that are located in North Pagelaran SubDistrict and Wargomulyo and Tanjung Russia, Pardasuka Sub-District. The research location was chosen purposively. There were 92 respondents in this study that was taken by simple random sampling.  Food coping strategies are analyzed by quantitative descriptive method with tabulation of data and relationship between household characteristics and food coping strategy is analyzed by Pearson correlation test.  The results of the study showed that food coping strategies used by the households were on the first and second scale.  On the first scale, households bought food from preferred to cheaper food, reduced amount of food consumed, and collect wild food or leaves that can be taken on the rice field/garden.  On the second scale, households buy food on credit and take household’s savings. Housewives are the most dominant perpetrators of food coping and all households are in the low category of food coping strategies.  There are negative relationship between food coping strategy and the number of family members, education level of patriarch, the availability of rice, asset, and food expenditure.   Keywords: food coping strategy, prosperous rice, food, rastra